Why the initial regulation of financial innovations is decisive: Regulatory arbitrage and off-balance-sheet leasing in Germany - Jan Friedrich; Matthias Thiemann (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2018)
This policy letter provides evidence for the crucial importance of the initial regulatory treatment for the further development of financial innovations by exploring the emergence and initial legal framing of off-balance-sheet leasing in Germany. Due to a missing legal framework, lease contracts occurred as an innovative social practice of off-balance-sheet financing. However, this lacking legal framing impeded the development of this financial innovation as it also created legal uncertainties. This was about to change after the initial legal framing of leasing in the 1970's which eliminated those legal uncertainties and off-balance-sheet leasing entered into a stunning period of growth while laying the foundation of a regulatory resiliency against efforts that seek to abandon the off-balance-sheet treatment of leases. As the initial legal framing is crucial for the further development of a financial innovation, we propose the French approach for the initial vindication of new financial products in which the principles-based rules are aligned with the capabilities of regulators to intervene, even when a financial innovation complies with the letter of the law. In this way, regulators could regulate the frontier of financial innovations and weed out those which are entirely or mainly driven by regulatory arbitrage considerations while maintaining the beneficial elements of those products.
urn:nbn:de:hebis:30:3-466844
Keywords: 330; financial innovations; regulation; regulatory arbitrage; leasing